Council of fire - Flint, Eric; Hunt, Walter H (The Arcane America series, 2019)
"The passage of Halley's Comet in 1759 is catastrophic. The comet appears to strike the Earth, sundering the New World from the Old. A chain of mountains rises in the Mid-Atlantic. No ship from the Old World arrives in America. No ship from the New World can find a passage to the Old-and most who try simply disappear. The comet has also unleashed magic forces, which soon spread everywhere. Slaves begin using powers derived from African witchcraft, bringing monsters from that continent into the New World. The native tribes begin doing the same. Some European settlers devise ways to couple Old World technology with sorcery. Kraken in the Atlantic, revenants in Jamaica, Dry Hands and Floating Heads in the Hudson valley, African ogres and worse set loose in the streets of New York. Magic of all kinds, emerging everywhere, most of it poorly if at all controlled. The powerful Iroquois Confederacy disintegrates. The Onondaga Council Fire is extinguished; the Seneca and Cayuga follow their own shaman and war leader, and the Mohawks ally with the English. For their part, the English and the French in North America, who had been on the brink of war when the Sundering came, now have to contemplate what would once have been unthinkable. They must not simply forge a military alliance against the rising dark powers but may even have to unite politically behind the young English prince Edward, now the only person of royal blood left in the terrifying world created by the Sundering"--